A bearing made of composite material

By using high -binding intensity composite materials and modifier corrosion, a wear -resistant and high temperature -resistant bearings are prepared to solve the problems of existing sliding bearing in friction and wear, and maintain anti -corrosion performance in high temperature environments.

CN118595440BActive Publication Date: 2025-01-24GUANGDONG SHAOZHU PRECISION FORGING CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410871146.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-01
Publication Date
2025-01-24
Estimated Expiration
2044-07-01

AI Technical Summary

Technical Problem

Existing sliding bearings are prone to failure due to friction and wear during use, and it is difficult to maintain corrosion resistance in high temperature environments.

Method used

The bearing is prepared by high -binding intensity composite materials, and it is made of mixing, sintering, rolling, resuscitation, and recovery process through the pre -pre -made body and CUSN8NI matrix powder. The corrosion of the cellulose derivatives is combined with the corrosion of the anticorrosion.

Benefits of technology

The problem of easy to fall off when diamond is solved, significantly improved the hardness of the composite materials, and maintained the anticorrosive effect of the corrosion agent in high temperature environments, and extended the life life of the bearings.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a bearing prepared with a high-bonding strength composite material, and belongs to the technical field of bearings. The present invention discloses a bearing prepared with a high-bonding strength composite material, wherein the preparation of the high-bonding strength composite material includes the following processes: diamond preform and CuSn8Ni matrix powder mixing-powder spreading-sintering-rolling-re-firing-re-rolling-impregnation corrosion inhibitor-high-bonding strength composite material, the diamond preform made of diamond as the core and metal material as the shell solves the problem of easy falling of diamond, and at the same time greatly improves the hardness of the composite material; the corrosion inhibitor prepared by modifying the cellulose derivative to improve its heat resistance, so that the corrosion inhibitor of the composite material will not lose its anti-corrosion effect at a higher temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bearings and relates to a bearing made of a composite material with high bonding strength. Background Art

[0002] Bearings are a type of component that plays an important role in mechanical equipment. Their purpose is to support mechanical rotating parts, reduce their friction coefficient during operation, and ensure that they have a certain rotation accuracy. Bearings are usually divided into rolling bearings and sliding bearings according to the different friction properties of the moving elements. Although sliding bearings reduce friction and wear and increase their lifespan by adding lubricants during actual use, they will be damaged and fail after a period of operation even under very good lubrication conditions. The various types of failure of sliding bearings can be summarized as scratches, abrasive wear, seizure, fatigue wear, peeling, corrosive wear, erosion, and micro-motion wear. Summary of the invention

[0003] The present invention relates to a bearing prepared with a high-bonding strength composite material, belonging to the technical field of bearings. The present invention discloses a bearing prepared with a high-bonding strength composite material, wherein the preparation of the high-bonding strength composite material includes the following processes: diamond preform and CuSn8Ni matrix powder mixing - powder spreading - sintering - rolling - re-firing - re-rolling - impregnation with corrosion inhibitor - high-bonding strength composite material, the diamond preform made of diamond as the core and metal material as the shell solves the problem of easy falling of diamond, and at the same time greatly improves the hardness of the composite material; the corrosion inhibitor prepared by modifying the cellulose derivative to improve its heat resistance, so that the corrosion inhibitor of the composite material will not lose its anti-corrosion effect at a higher temperature.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A bearing made of a high-bonding strength composite material. The preparation method of the bearing of the high-bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and then put into a high-temperature sintering furnace, and nitrogen is introduced for sintering, and then taken out for rolling, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high-bonding strength composite material and a bearing, and then immersed in a corrosion inhibitor, and dried to obtain a bearing of the high-bonding strength composite material.

[0006] Furthermore, the preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into particles of 30-60 mesh, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0007] Furthermore, the mass content of Gr in the Cr-diamond particles is 20-30%, and the weight ratio of the Cr-diamond particles to the alloy powder is 1-3:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0008] Furthermore, the preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve it to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then sodium hydroxide solution is added to neutrality, cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain a corrosion inhibitor.

[0009] Furthermore, the solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1, and the time and temperature in the constant temperature box are 2-3 h and 45-55° C., respectively.

[0010] Furthermore, the mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 1-4:20 mL, the heating temperature is 70-80° C., the mass concentration of the sodium hydroxide solution is 20-30%, and the solid-liquid ratio of the solid to ethanol is 100-200:1 g / L.

[0011] Furthermore, the mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:10-20, wherein the mesh size of the CuSn8Ni matrix powder is 120-150 meshes, and the thickness of the preform laid on the cold-rolled carbon structural steel plate is 0.5-1 mm.

[0012] Furthermore, the sintering temperature is 840-860°C, and the re-firing temperature is 860-880°C.

[0013] Beneficial effects of the present invention:

[0014] 1. Diamond preform and CuSn8Ni matrix powder are mixed - powdered - sintered - rolled - re-fired - re-rolled - impregnated with corrosion inhibitor - high bonding strength composite material. The diamond preform is made of diamond as the core and metal material as the shell, which solves the problem of easy falling of diamond and greatly improves the hardness of the composite material. The corrosion inhibitor is prepared by modifying the cellulose derivative to improve its heat resistance, so that the corrosion inhibitor will not lose its anti-corrosion effect at a higher temperature. DETAILED DESCRIPTION

[0015] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with embodiments.

[0016] Example 1

[0017] A bearing made of a high-bonding strength composite material. The preparation method of the bearing of the high-bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and then put into a high-temperature sintering furnace, and nitrogen is introduced for sintering, and then taken out for rolling, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high-bonding strength composite material and a bearing, and then immersed in a corrosion inhibitor, and dried to obtain a bearing of the high-bonding strength composite material.

[0018] The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into 50-mesh particles, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0019] The mass content of Gr in the Cr-diamond particles is 20%, and the weight ratio of the Cr-diamond particles to the alloy powder is 1:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0020] The preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutrality, the mixture is cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain the corrosion inhibitor.

[0021] The solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1, and the time and temperature in the constant temperature box are 2 hours and 45° C., respectively.

[0022] The mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 1:20 mL, the heating temperature is 70° C., the mass concentration of the sodium hydroxide solution is 20%, and the solid-liquid ratio of the solid to ethanol is 100:1 g / L.

[0023] The purchase source of the di(2-chloroethyl)amine hydrochloride is: di(2-chloroethyl)amine hydrochloride / Xinmingtai / 821-48-7, and the mass concentration of the hydrochloric acid is 35%.

[0024] The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:10, wherein the mesh number of the CuSn8Ni matrix powder is 120 meshes, and the thickness of the preform laid on the cold-rolled carbon structural steel plate is 0.5 mm.

[0025] The sintering temperature is 840°C, and the re-firing temperature is 860°C.

[0026] Example 2

[0027] A bearing made of a high-bonding strength composite material. The preparation method of the bearing of the high-bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and then put into a high-temperature sintering furnace, and nitrogen is introduced for sintering, and then taken out for rolling, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high-bonding strength composite material and a bearing, and then immersed in a corrosion inhibitor, and dried to obtain a bearing of the high-bonding strength composite material.

[0028] The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into 50-mesh particles, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0029] The mass content of Gr in the Cr-diamond particles is 25%, and the weight ratio of the Cr-diamond particles to the alloy powder is 2:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0030] The preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutrality, the mixture is cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain the corrosion inhibitor.

[0031] The solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1, and the time and temperature in the constant temperature box are 2.5 h and 50° C., respectively.

[0032] The mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 2.5:20 mL, the heating temperature is 75° C., the mass concentration of the sodium hydroxide solution is 25%, and the solid-liquid ratio of the solid to ethanol is 150:1 g / L.

[0033] The purchase source of the di(2-chloroethyl)amine hydrochloride is: di(2-chloroethyl)amine hydrochloride / Xinmingtai / 821-48-7, and the mass concentration of the hydrochloric acid is 35%.

[0034] The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:15, wherein the mesh number of the CuSn8Ni matrix powder is 135 meshes, and the thickness of the preform on the cold-rolled carbon structural steel plate is 0.8 mm.

[0035] The sintering temperature is 850°C, and the re-firing temperature is 870°C.

[0036] Example 3

[0037] A bearing made of a high-bonding strength composite material. The preparation method of the bearing of the high-bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and then put into a high-temperature sintering furnace, and nitrogen is introduced for sintering, and then taken out for rolling, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high-bonding strength composite material and a bearing, and then immersed in a corrosion inhibitor, and dried to obtain a bearing of the high-bonding strength composite material.

[0038] The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into 30-mesh particles, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0039] The mass content of Gr in the Cr-diamond particles is 30%, and the weight ratio of the Cr-diamond particles to the alloy powder is 3:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0040] The preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutrality, the mixture is cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain the corrosion inhibitor.

[0041] The solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1, and the time and temperature in the constant temperature box are 3 hours and 55° C., respectively.

[0042] The mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 4:20 mL, the heating temperature is 80° C., the mass concentration of the sodium hydroxide solution is 30%, and the solid-liquid ratio of the solid to ethanol is 200:1 g / L.

[0043] The purchase source of the di(2-chloroethyl)amine hydrochloride is: di(2-chloroethyl)amine hydrochloride / Xinmingtai / 821-48-7, and the mass concentration of the hydrochloric acid is 35%.

[0044] The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:20, wherein the mesh size of the CuSn8Ni matrix powder is 150 meshes, and the thickness of the preform on the cold-rolled carbon structural steel plate is 1 mm.

[0045] The sintering temperature is 860°C, and the re-firing temperature is 880°C.

[0046] Comparative Example 1

[0047] On the basis of Example 2, a bearing is prepared with a high bonding strength composite material. The preparation method of the bearing of the high bonding strength composite material is as follows: diamond is mixed with CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, put into a high-temperature sintering furnace, and nitrogen is introduced for sintering at the same time, taken out and rolled, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high bonding strength composite material and made into a bearing, immersed in a corrosion inhibitor, and dried to obtain a bearing of a high bonding strength composite material.

[0048] The preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutrality, the mixture is cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain the corrosion inhibitor.

[0049] The solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1, and the time and temperature in the constant temperature box are 2.5 h and 50° C., respectively.

[0050] The mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 2.5:20 mL, the heating temperature is 75° C., the mass concentration of the sodium hydroxide solution is 25%, and the solid-liquid ratio of the solid to ethanol is 150:1 g / L.

[0051] The purchase source of the di(2-chloroethyl)amine hydrochloride is: di(2-chloroethyl)amine hydrochloride / Xinmingtai / 821-48-7, and the mass concentration of the hydrochloric acid is 35%.

[0052] The mass ratio of the diamond to the CuSn8Ni matrix powder is 1:15, wherein the mesh size of the CuSn8Ni matrix powder is 135 meshes, and the thickness of the powder spread on the cold-rolled carbon structural steel plate is 0.8 mm.

[0053] The sintering temperature is 850°C, and the re-firing temperature is 870°C.

[0054] Comparative Example 2

[0055] On the basis of Example 2, a bearing is prepared with a high bonding strength composite material. The preparation method of the bearing of the high bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and put into a high-temperature sintering furnace, and nitrogen is introduced at the same time for sintering, and then taken out for rolling, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high bonding strength composite material and made into a bearing, that is, a bearing of a high bonding strength composite material.

[0056] The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into 50-mesh particles, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0057] The mass content of Gr in the Cr-diamond particles is 25%, and the weight ratio of the Cr-diamond particles to the alloy powder is 2:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0058] The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:15, wherein the mesh number of the CuSn8Ni matrix powder is 135 meshes, and the thickness of the preform on the cold-rolled carbon structural steel plate is 0.8 mm.

[0059] The sintering temperature is 850°C, and the re-firing temperature is 870°C.

[0060] Comparative Example 3

[0061] On the basis of Example 2, a bearing is prepared with a high bonding strength composite material. The preparation method of the bearing of the high bonding strength composite material is as follows: a diamond preform is mixed with a CuSn8Ni matrix powder, and then spread on a cold-rolled carbon structural steel plate, and put into a high-temperature sintering furnace, and nitrogen is introduced for sintering at the same time, and the preform is taken out and rolled, and then put into the sintering furnace for re-firing, and then taken out and re-rolled to form a high bonding strength composite material and a bearing, and then immersed in a corrosion inhibitor, and dried to obtain a bearing of a high bonding strength composite material.

[0062] The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into 50-mesh particles, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform.

[0063] The mass content of Gr in the Cr-diamond particles is 25%, and the weight ratio of the Cr-diamond particles to the alloy powder is 2:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:1.

[0064] The preparation method of the corrosion inhibitor is as follows: hydroxyethyl cellulose and di(2-chloroethyl)amine hydrochloride are mixed, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutralize the mixture, the mixture is cooled and washed with distilled water, the mixture is dried to form a solid, and ethanol is added to mix the mixture to obtain the corrosion inhibitor.

[0065] The mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, the solid-liquid ratio of the total mass of the two to hydrochloric acid is 2.5:20 mL, the heating temperature is 75° C., the mass concentration of the sodium hydroxide solution is 25%, and the solid-liquid ratio of the solid to ethanol is 150:1 g / L.

[0066] The purchase source of the di(2-chloroethyl)amine hydrochloride is: di(2-chloroethyl)amine hydrochloride / Xinmingtai / 821-48-7, and the mass concentration of the hydrochloric acid is 35%.

[0067] The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:15, wherein the mesh number of the CuSn8Ni matrix powder is 135 meshes, and the thickness of the preform on the cold-rolled carbon structural steel plate is 0.8 mm.

[0068] The sintering temperature is 850°C, and the re-firing temperature is 870°C.

[0069] Performance Testing

[0070] 1. The high bonding strength composite materials prepared in Examples 1-3 and Comparative Example 1 were used as samples, and the wear performance and surface morphology of the samples were analyzed using a HDM-20 end face friction and wear tester and an optical microscope. The experiment used a silicon nitride ball as a friction pair with a Rockwell hardness (HRC) of 78 and a diameter of 6.35 mm. The experimental parameters used in the friction and wear tester were set as follows: load pressure 200 N, friction ball speed 200 r / min, and time 360 ​​s.

[0071] 2. The bearings prepared in Examples 1-2 and Comparative Examples 2-3 were used as samples. The samples were weighed before the experiment and then placed in 1 mol / L hydrochloric acid for 5 hours. Example 2 and Comparative Example 3 were heated to 80°C and weighed again after the test. The corrosion inhibition rate of the sample was calculated, specifically, corrosion inhibition rate = (w1-w2) / w1×100%, where w1 is the weight before the experiment and w2 is the weight after the experiment.

[0072] The test results are shown in Table 1 and Table 2.

[0073] Table 1 Test results

[0074] Sample Wear resistance / times Surface morphology Example 1 13.80 No scratches Example 2 14.02 No scratches Example 3 13.90 No scratches Comparative Example 1 8.03 Scratches

[0075] It can be seen from Table 1 that the wear resistance of Examples 1-3 is better than that of Comparative Example 1. The diamond in Comparative Example 1 has not been prefabricated, and the fusion with the matrix powder is poor, and it is easy to fall off, thereby affecting the wear resistance.

[0076] Table 2 Test results

[0077] Sample Corrosion inhibition rate% Example 1 99.23 Comparative Example 2 95.15 Example 2 98.12 Comparative Example 3 93.30

[0078] It can be concluded from Table 2 that the corrosion inhibition rate of Example 1 is greater than that of Comparative Example 2, and the corrosion inhibition rate of Example 2 is greater than that of Comparative Example 3. In Comparative Example 2, no corrosion inhibitor was impregnated, and its corrosion resistance was worse than that of Example 1; the corrosion inhibitor used in Comparative Example 3 was not modified, and its corrosion resistance was basically invalid at a relatively high temperature.

[0079] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A bearing made of a composite material, characterized in that: The preparation method of the bearing comprises: mixing a diamond preform with a CuSn8Ni matrix powder, spreading the mixture on a cold-rolled carbon structural steel plate, placing the mixture in a high-temperature sintering furnace, introducing nitrogen gas for sintering, taking the mixture out for rolling, placing the mixture in a sintering furnace for re-firing, taking the mixture out for re-rolling to form a high-bonding strength composite material and making the bearing, impregnating the mixture in a corrosion inhibitor, and drying the mixture to obtain a bearing made of the high-bonding strength composite material; The preparation method of the diamond preform is as follows: diamond particles are plated with Cr on their surfaces by passing an electric current to form Cr-diamond particles, which are then mixed with alloy powder in a mixing tank filled with nitrogen for 2 hours, the mixed powder is made into particles of 30-60 mesh, the particles are placed in a vacuum oven, and heated at 1800°C and a vacuum degree of 10 -1 Pa for 2 h, and then naturally cooled to obtain a diamond preform; The preparation method of the corrosion inhibitor is as follows: distilled water is added to hydroxyethyl cellulose to dissolve to form a mixed solution, sodium periodate is added, the mixture is stirred and placed in a constant temperature box, and then washed with distilled water to make it neutral, dried to obtain a white powder, the white powder is mixed with di(2-chloroethyl)amine hydrochloride, hydrochloric acid is added, the temperature is increased, and then a sodium hydroxide solution is added to neutrality, the mixture is cooled and washed with distilled water, dried to form a solid, and ethanol is added to mix to obtain the corrosion inhibitor; The solid-liquid ratio of the hydroxyethyl cellulose to distilled water is 4:1 g / L, the mass ratio of the hydroxyethyl cellulose to sodium periodate is 20:1; the mass ratio of the white powder to di(2-chloroethyl)amine hydrochloride is 1:1.5, and the solid-liquid ratio of the total mass of the two to hydrochloric acid is 1-4:20 g / mL.

2. A bearing made of composite material according to claim 1, characterized in that: The mass content of Cr in the Cr-diamond particles is 20-30%, and the weight ratio of the Cr-diamond particles to the alloy powder is 1-3:10, wherein the alloy powder is composed of iron, chromium, boron and silicon in a mass ratio of 1:1:1:

1.

3. A bearing made of composite material according to claim 1, characterized in that: In the preparation of the corrosion inhibitor, the time and temperature in the constant temperature box are 2-3h and 45-55°C respectively.

4. A bearing made of composite material according to claim 1, characterized in that: In the preparation of the corrosion inhibitor, the heating temperature is 70-80° C., the mass concentration of the sodium hydroxide solution is 20-30%, and the solid-liquid ratio of the solid to ethanol is 100-200:1 g / L.

5. A bearing made of composite material according to claim 1, characterized in that: The mass ratio of the diamond preform to the CuSn8Ni matrix powder is 1:10-20, wherein the mesh number of the CuSn8Ni matrix powder is 120-150 meshes, and the thickness of the preform laid on the cold-rolled carbon structural steel plate is 0.5-1 mm.

6. A bearing made of composite material according to claim 1, characterized in that: The sintering temperature is 840-860°C, and the re-firing temperature is 860-880°C.

Citation Information

Patent Citations

  • Polishing solution for ceramic bearing balls and preparation method thereof

    CN112521865A

  • Diamond-containing super wear-resistant nickel-based composite material and preparation method thereof

    CN115971475A